HISAB FALAK DAN RU'YAH HILAL (Antara Misi Ilmiah dan Seruan Ta’abbud) - Shofiyullah Mukhlas (IAIN Pekalongan, 2009)
Calculation of moon rotation and seeing crescent often give different result of the condition and position of the crescent. This makes many scholars have different opinion of the calculation of moon rotation and seeing crescent role in deciding the first date of Islamic month. Is only the calculation of moon rotation qualified? Or is only the seeing crescent qualified? Or the both are qualified? However, the opinion to using the both, even though the result is different, is better than using only one of them. It is because by using the both, the condition and position of the crescent can be made sure, so that the causal factor of different result can be certain. This article tries to promote to use the both in deciding the first date of Islamic month. The calculation of moon rotation is only an instrument to make sure that seeing crescent can be done accurately.